2011
DOI: 10.1021/ol2027224
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Total Synthesis of (±)-Minfiensine

Abstract: A concise total synthesis of (±)-minfiensine using all conventional methods and starting from commercial materials has been completed. The synthesis features a Fischer indole synthesis, a Heck alkylation of an intermediate ketone enolate, conversion of a ketone carbonyl into an epoxide, and transformation of the latter into an allylic alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…It was found that the regioselectivity of the ring‐opening reaction highly depends on the reagents used (Table ). Treatment of epoxide 12 with TMSOTf/DBU led to only minor conversion, and the undesired regioisomer 14 was the major product (entry 1). To increase the selectivity by favoring proton abstraction at the less hindered C2 of the ring system, a sterically hindered Lewis acid/base pair, Al(O i Pr) 3 was employed .…”
Section: Figurementioning
confidence: 99%
“…It was found that the regioselectivity of the ring‐opening reaction highly depends on the reagents used (Table ). Treatment of epoxide 12 with TMSOTf/DBU led to only minor conversion, and the undesired regioisomer 14 was the major product (entry 1). To increase the selectivity by favoring proton abstraction at the less hindered C2 of the ring system, a sterically hindered Lewis acid/base pair, Al(O i Pr) 3 was employed .…”
Section: Figurementioning
confidence: 99%
“…Lapidilectine B, grandilodine C [22], and lundurine B exhibit multidrug resistance (MDR) in vincristine-resistant KB cancer cells [2324]. Minfiensine alkaloid [2531] containing a novel 1,2,3,4-tetrahydrocarbazole ring skeleton shows anticancer activity [32]. König and co-workers identified some propellane derivatives as cannabinoid CB 1 receptor antagonists [33], which are potential drugs for the treatment of schizophrenia and alcohol addiction [34].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the retrosynthetic analysis,o ur synthesis of (+ +)-flavisiamine F( 1)c ommenced with the protected carbazolone 5,w hich was prepared from carbazole-3,2'-[1,3]dioxolane [10] by introducing the phenylsulfonyl group in basic conditions followed by acidic deprotection. Reaction with LiHMDS and Hendrickson-McMurray reagent afforded the triflate 6 as shown in Scheme 2.…”
mentioning
confidence: 99%